Features of Developing an Individual Rehabilitation Program for Middle School-Aged Children with Scoliosis of the 2nd Degree - Stretovych, Olena; Antonova-Rafi , Yulia (The Ukrainian Scientific Medical Youth Journal, 2024)
scoliosis is a common orthopedic disorder affecting 5-9% of children, with severe spinal deformities accounting for 0.5-0.6% of cases. As spinal deformities progress, the shape of the chest and pelvis inevitably changes. The pathological process involves the heart, lungs, abdominal organs, and pelvic organs, leading to compromised respiratory function and hemodynamics. In advanced cases, nerve root tension, radiating pain, and, in some patients, compression of the spinal cord and spastic paralysis may develop. Type C scoliosis manifests with a single curve and may occur after spine injury, tuberculous spondylitis, or as the initial presentation of scoliosis (idiopathic). Idiopathic or adolescent scoliosis is most prevalent in middle school-aged children, constituting 70-80% of all pediatric spinal deformities. The earlier scoliosis develops, indicating a younger patient, the greater the growth potential and likelihood of deformity progression. The most critical age range for scoliosis development is 10-13 years. This article addresses key issues related to spine mobility in individuals with C-type scoliosis in middle school-aged children. Additionally, a rehabilitation methodology is presented, incorporating post-isometric relaxation methods into the standard physical therapy program for those with C-type scoliosis. The proposed methodology aims to slow the progression of the condition, enhance mobility across all spinal segments, reduce pain syndrome, and stabilize overall health. To evaluate the effectiveness of the developed physical therapy program for patients with C-type scoliosis, a study was conducted with 20 participants observed at the Municipal Non-Profit Enterprise "Kyiv Diagnostic Center for Children" in Darnytskyi district, Kyiv.